Getting Students to Stick Around: The Effects of Completing an Introductory Course on Persistence for Community College Students - Dora Gicheva; Julie Edmunds; Marie C. Hull; Beth Thrift (Institute of Labor Economics (IZA), 2022)
This paper studies the impacts of withdrawing from and failing a course, relative to successful completion, on persistence for community college students. We leverage random assignment of students to instructors for identification. Withdrawing from a course reduces the probability of persistence by about 20 percentage points, while the impact of failing is much smaller in magnitude and statistically indistinguishable from zero. Course withdrawals are highly correlated with full institutional withdrawal for the students in our sample, which is in turn linked to lower likelihood of returning the following semester. Our findings reinforce the importance of academic momentum: remaining in a course keeps students attached to college even if they earn a failing grade.
Keywords: I21; I23; 330; community college; persistence; course completion; instructor effects